PREVALENCE AND ANTIBIOTIC SUSCEPTIBILITY PATTERN OF HIGH LEVEL AMINOGLYCOSIDE RESISTANCE AMONG GRAM POSITIVE ORGANISMS IN A TERTIARY CARE CENTRE - A., DIVYA PRABHA; NAIR, POOJA; UMAMAGESWARI, S. S. M.; MONICA, R.; VENNILA, ROSY (International Journal of Current Pharmaceutical Research, 2021)
Objective: The study is done to determine the prevalence and the antimicrobial susceptibility against the gram positive organisms with high level amino glycosides resistance. Methods: This is a prospective study involving the analysis of clinical samples for gram positive organisms like Streptococcus species, Enterococcus species and Staphylococcus species and determining their antimicrobial susceptibility pattern. Results: From the collected clinical samples, all the gram positive organisms show resistance to gentamicin. Most of the Staphylococcus species showed a wide resistance to erythromycin followed by ceftrioxazone and many Enterococcus species shows resistance to penicillin, erythromycin, ciprofloxacin. Conclusion: The high level aminoglycoside resistant (HLAR) gram positive organisms showed susceptibility to few drugs that are prevalent in various clinical samples. Surveillance of antimicrobial resistance and sensitivity is essential in managing and control of infection.